Functional Disruption of a Chloroplast Pseudouridine Synthase Desensitizes Arabidopsis Plants to Phosphate Starvation - Lu, Shan; Li, Chenyi; Zhang, Ye; Zheng, Zai; Liu, Dong (Frontiers in Plant Science, 2017)
Phosphate (Pi) deficiency is a common nutritional stress of plants in both agricultural and natural ecosystems. Plants respond to Pi starvation in the environment by triggering a suite of biochemical, physiological, and developmental changes that increase survival and growth. The key factors that determine plant sensitivity to Pi starvation, however, are unclear. In this research, we identified an Arabidopsis mutant, dps1, with greatly reduced sensitivity to Pi starvation. The dps1 phenotypes are caused by a mutation in the previously characterized SVR1 (SUPPRESSION OF VARIAGATION 1) gene, which encodes a chloroplast-localized pseudouridine synthase. The mutation of SVR1 results in defects in chloroplast rRNA biogenesis, which subsequently reduces chloroplast translation. Another mutant, rps5, which contains a mutation in the chloroplast ribosomal protein RPS5 and has reduced chloroplast translation, also displayed decreased sensitivity to Pi starvation. Furthermore, wild type plants treated with lincomycin, a chemical inhibitor of chloroplast translation, showed similar growth phenotypes and Pi starvation responses as dps1 and rps5. These results suggest that impaired chloroplast translation desensitizes plants to Pi starvation. Combined with previously published results showing that enhanced leaf photosynthesis augments plant responses to Pi starvation, we propose that the decrease in responses to Pi starvation in dps1, rps5, and lincomycin-treated plants is due to their reduced demand for Pi input from the environment.